Analisis Pengaruh Organizational Citizenship Behavior Dan Komitmen Organisasi Terhadap Kinerja Karyawan Pada PT. Sumber Karindo Sakti - Siregar, Jansen Alanuari; Suci Etri Jayanti. S (Sekolah Tinggi Ilmu Ekonomi Bina Karya, 2022)
The research objective that researchers are currently conducting is to analyze and find out how much Organizational Citizenship Behavior (X1) and Organizational Commitment (X2) have an impact on Employee Performance (Y) at PT. Sumber Karindo Sakti either partially or simultaneously. The method of determining the sample size using the slovin formula as many as 68 samples, namely employees of PT. Sumber Karindo Sakti is a casual daily worker. From the processed data, it is clear that hypothesis 1 is accepted, which means that the Organizational Citizenship Behavior variable (X1) has an influence on Employee Performance (Y), hypothesis 2 is rejected, which means that the Organizational Commitment variable (X2) has no effect on Employee Performance (Y), and hypothesis 3 is accepted, which means that the Organizational Citizenship Behavior (X1) and Organizational Commitment (X2) variables have a simultaneous effect on the Employee Performance variable (Y).